Criminalistic innovations and their implementation in the practice of the investigator - Khlus, Alexander M. (Journal of the Belarusian State University. Law, 2022)
The innovative forensic activity is considered in the article. On the example of the achievements of the scientific school of forensic science, which was headed by professor A. V. Dulov, the possibilities of introducing the recommendations of forensic science into the practice of investigating crimes are shown. The emphasis is made on the problem of methodological support of investigative activity in the aspect of its improvement on the basis of innovative developments of the scientific school of forensic science. The drawbacks of the existing methods of investigating crimes are shown. Developed on the basis of the forensic characterisation of crimes, private investigation methods do not meet the needs of the time, since the forensic characterisation itself is not a perfect scientific category. It is proposed to form private methods of investigation, based on the initial identification and further characteristics (description) of the material elements that make up the structure of crimes. It is concluded that the material structure of the crime, combined with the forensic characteristics of its elements, gives the most complete picture of the information model of a specific type of criminal act, on the basis of which private investigation methods should be formed.
Keywords: crime; crime investigation; forensic science; private investigation technique; forensic characteristics; material structure